The Education of A Recidivist Family (A Case Study of X Family at Kelurahan Lubuk Buaya, Kecamatan Koto Tangah, Kota Padang) - Nindi Nilam Sari; Syafruddin Wahid; Wisroni Wisroni (Universitas Negeri Padang, 2019)
The purpose of this research is to describe in a family educator, learner in the family, learning objectives, materials, methods of learning and the learning environment in the family of a recidivist at Kelurahan Lubuk Buaya Kecamatan Koto Tangah Kota Padang. This research used the method of qualitative research in the form of a case study. The data collection technique using snowball sampling. The collected data through observation and interviews. Analysis of the data using qualitative analysis data. The proses of analysis data are data reduction, data display, and verification. Based on the results of this research concluded that educator in the family is the recidivist, learners in a recidivist family is his wife and the child, the learning goal is for the children to have manners as the foundation of his life. The materials are honesty and openness, religion and manners, responsibility, shaping of our thinking. The learning environment is the family, community and natural surroundings.Keywords: Education, Family, Recidivist